Electromagnetic protection plate and preparation method thereof
By using carbonized gelling materials and other ingredients to prepare electromagnetic protection plates, the problem of poor comprehensive performance of existing cement-based electromagnetic shielding materials in electromagnetic shielding and mechanical properties is solved, and efficient and economical electromagnetic shielding and mechanical properties are achieved, and the preparation process is simplified.
Patent Information
- Application Number
- CN202310374708.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-10
AI Technical Summary
The existing cement-based electromagnetic shielding materials have poor comprehensive performance in electromagnetic shielding and mechanical properties, and the preparation process is complicated and the molding time is long.
Carbonized gelling materials are used as the main cementitious material components, combined with cement, inert fillers, conductive fillers, foaming agents and foam stabilizing agents, electromagnetic protective plates are prepared through simple mixing and pouring processes, and carbon dioxide is cured during the carbonization and curing process.
It realizes the excellent electromagnetic shielding performance and excellent mechanical properties of the electromagnetic protective plate. The preparation process is simplified, the cost is low, and the curing time is short, which is in line with the concept of green energy conservation and emission reduction.
Smart Images

Figure BDA0004169942180000111 
Figure BDA0004169942180000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to an electromagnetic protection plate and a preparation method thereof. Background Art
[0002] Due to the popularity of electronic information equipment in modern society, electronic pollution such as electromagnetic radiation and electromagnetic interference has become ubiquitous in people's daily lives. Long-term exposure to electromagnetic radiation can cause serious harm to the human body. The World Health Organization has listed electromagnetic radiation as the fourth largest source of environmental pollution after air, water, and noise. In order to reduce the harm of electromagnetic radiation to a certain extent, domestic and foreign scholars have conducted a lot of research on electromagnetic shielding materials, among which cement-based electromagnetic shielding materials are an important component.
[0003] However, the most studied cement-based electromagnetic shielding materials are cement-based electromagnetic shielding materials filled with metal or carbon materials, which have good reflective electromagnetic shielding performance at the low frequency end by improving the electrical conductivity. The current difficulty is that reflective electromagnetic shielding does not completely eliminate the hazards of electromagnetic shielding and may cause secondary pollution. Therefore, a large number of scholars have studied porous materials such as foam concrete, trying to introduce porous structures to improve the material's wave absorption performance. However, traditional foam concrete generally has low mechanical strength, a complex molding process, and a long molding time. In summary, how to prepare a porous electromagnetic protection material with a new material as the main body, which not only has excellent electromagnetic shielding performance, but also simplifies the preparation process and strengthens its mechanical properties, is an urgent problem to be solved. Summary of the invention
[0004] The purpose of the present invention is to overcome the above technical deficiencies, provide an electromagnetic protection plate and a preparation method thereof, and solve the technical problem that the electromagnetic shielding and mechanical comprehensive performance of the electromagnetic protection plate in the prior art are poor.
[0005] In order to achieve the above technical purpose, the technical solution of the present invention is:
[0006] In a first aspect, the present invention provides an electromagnetic protection plate, comprising the following raw materials: 60 to 80 parts of carbonized cementitious material, 20 to 40 parts of cement, 10 to 20 parts of inert filler, 1.5 to 2 parts of water reducer, 1 to 5 parts of conductive filler, 0.1 to 0.25 parts of foaming agent, 0.03 to 0.08 parts of foam stabilizer and several parts of water.
[0007] In a second aspect, the present invention provides a method for preparing an electromagnetic protection plate, comprising the following steps:
[0008] mixing carbonized cementitious material, cement, inert filler, water reducing agent and conductive filler to obtain an initial slurry;
[0009] Mixing a foaming agent, a foam stabilizer and water to prepare foam;
[0010] Mixing the initial slurry with the foam to obtain a target slurry;
[0011] The target slurry is sequentially cast, cured, demoulded and carbonized to obtain the electromagnetic protection plate.
[0012] Compared with the prior art, the beneficial effects of the present invention include:
[0013] The preparation method of the present invention is simple, requires few types of raw materials, has low cost, and short curing time, which is only one-third to one-quarter of the cement-based electromagnetic shielding plate; it has excellent mechanical properties, and the dry density is 750kg / m 3 The strength of the standard test block can reach more than 5.8MPa in three days; the preparation process can simultaneously solidify carbon dioxide, and each cubic meter of material can absorb up to 95kg of CO2, which is in line with the concept of green energy conservation and emission reduction;
[0014] At the same time, the electromagnetic protection plate provided by the present invention has good shielding performance in both low-frequency and high-frequency bands of electromagnetic waves, with an absorption band of 6.3 to 10.4 GHz above 10 dB and an absorption band of 1.6 to 4.8 GHz above 20 dB, and can serve in different electromagnetic radiation environments; at the same time, it is lightweight, high-strength, thermally insulating, and has a thermal conductivity of 0.13 to 0.17 W / m·k, and can be used as a building exterior wall with excellent electromagnetic shielding performance. DETAILED DESCRIPTION
[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0016] The present invention provides an electromagnetic shielding plate and a method for preparing the same, comprising the following aspects:
[0017] The first aspect of the present invention provides a carbon mineralized electromagnetic protection plate, which is composed of the following raw materials in parts by weight: 60 to 80 parts of carbonized cementitious material, 20 to 40 parts of cement, 10 to 20 parts of inert filler, 1.5 to 2 parts of polycarboxylic acid water reducer, 1 to 5 parts of conductive filler, 0.1 to 0.25 parts of foaming agent, 0.03 to 0.08 parts of foam stabilizer and 25 to 55 parts of water.
[0018] Furthermore, the carbonized cementitious material is one or more of γ-type dicalcium silicate, monocalcium silicate, tricalcium disilicate, steel slag, and magnesium slag; preferably, the carbonized cementitious material is γ-C2S.
[0019] Furthermore, the cement is ordinary Portland cement with a grade of ≥42.5, and the initial setting time of the cement is ≥45 minutes, the final setting time is ≤10 hours, and the fineness is <80 μm.
[0020] Furthermore, the inert filler includes one or more of fly ash, quartz sand powder and limestone powder.
[0021] The present invention selects the above-mentioned carbonized cementitious material with lower hydration activity and higher carbonization activity as the main cementitious material component, so that the board can absorb and solidify a large amount of CO2 to form excellent mechanical strength; a small amount of cement is used to give the board basic strength before carbonization curing, which is convenient for demolding operation; the role of a small amount of inert filler is to enhance the volume stability of the board and prevent sedimentation during the preparation process.
[0022] Furthermore, the selected γ-C2S is a powder with a particle size distribution of 0.5 to 100 μm and an apparent density of 2.8 to 3.0 g / cm 3 . Furthermore, γ-C2S is made by high-temperature sintering of calcium raw materials and silicon raw materials. Among them, the calcium raw material is calcium hydroxide, calcium carbonate or raw materials rich in calcium hydroxide and calcium carbonate (such as carbide slag, limestone powder, thiourea slag, monocyanamide slag, etc.), and the silicon raw material is silicon dioxide or raw materials rich in silicon dioxide (such as quartz stone powder, sandstone, quartz sand tailings, gold tailings, etc.). The calcium raw material and the silicon raw material are mixed at a molar ratio of 2:1 of equivalent calcium oxide: silicon dioxide, and then water is added to stir evenly and dry, and then sintered at a temperature of 1300-1400°C.
[0023] Preferably, the polycarboxylate water reducer is a polycarboxylate water reducer with a solid content of ≥30%. In the present invention, by adding the polycarboxylate water reducer, it can be adsorbed on the surface of the particles, and the particles are prevented from agglomerating through the combined effects of charge repulsion and steric hindrance, thereby improving the dispersion performance. Furthermore, the water reduction rate of the selected polycarboxylate water reducer is 25-35%.
[0024] In the present invention, the conductive filler is one or more of chopped carbon fiber and graphite powder. The carbon fiber has a diameter of 0.5-0.7 μm, a length of 3-5 mm, and a resistivity of 1.0-1.3 Ω / cm; and the graphite powder is an analytically pure reagent.
[0025] In the present invention, the foaming agent is one or more of a plant protein foaming agent, an animal protein foaming agent, and an air entraining agent; preferably, the foaming agent is a plant protein foaming agent; and the foam stabilizer is hydroxypropyl methylcellulose with a viscosity of 100000 Cst.
[0026] Preferably, the mass ratio of the foaming agent to water is 1:(40-60).
[0027] A second aspect of the present invention provides a method for preparing a carbon mineralized electromagnetic protection plate, comprising the following steps:
[0028] S1: mixing the carbonized gelling material, cement, inert filler, water and water reducing agent, stirring for 0.5 to 3 minutes to obtain slurry A, adding conductive filler and stirring to obtain initial slurry B;
[0029] S2: Mixing a foaming agent, a foam stabilizer and water, and preparing foam using a foaming machine;
[0030] S3: mixing the initial slurry B with the foam to obtain a target slurry;
[0031] S4: pouring and curing the target slurry in a mold, carbonizing and curing the slurry after demoulding, and obtaining a carbon mineralized electromagnetic shielding plate after curing.
[0032] The method for preparing the carbon mineralized electromagnetic shielding plate provided in the second aspect of the present invention is used to obtain the carbon mineralized electromagnetic shielding plate provided in the first aspect of the present invention.
[0033] In the present invention, the order of adding the components needs to be strictly controlled to avoid uneven dispersion of the conductive filler in the slurry, thereby affecting the electromagnetic shielding performance.
[0034] According to the present invention, in the above steps, the stirring speed is 100-150 r / min, S1 is stirred for 1 min to obtain slurry A, and stirred for 20-40 s to obtain initial slurry B; S3 stirring time is 20-40 s. Under this condition, the solid particles can be fully dispersed, the conductive filler can be fully dispersed, and the foam and slurry can be evenly mixed.
[0035] Preferably, in step S1, if the conductive filler is chopped carbon fiber, slurry A must be formed first and then the chopped carbon fiber is added; if graphite powder is used as the conductive filler, there is no requirement for the order of addition, that is, it can be directly mixed with carbonized gelling materials, etc., or it can be added to slurry A later.
[0036] Preferably, the mass ratio of the initial slurry to the foam is 10:(0.6-0.9); more preferably, it is 10:(0.7-0.8).
[0037] More preferably, the foaming agent, the foam stabilizer and water are mixed in a mass ratio of 1:(0.3-0.6):50, and the foam is prepared in a foaming machine, and can exist relatively stably within ten minutes.
[0038] In the present invention, the thickness of the prepared carbon mineralized electromagnetic protection plate is 20 mm.
[0039] According to the present invention, during the pouring process, a scraper is used to scrape out the slurry that is higher than the edge of the mold to ensure that a plate of standard size is obtained.
[0040] According to the present invention, the above-mentioned curing conditions are: standing in a forced air drying oven at a temperature of 30-50° C. for 2 days, forming basic strength through the hydration activity of a small amount of cement, so that demoulding can be carried out smoothly.
[0041] According to the present invention, the carbonization curing conditions are as follows: carbonization temperature of 5-40°C, relative humidity of 10-60%, carbon dioxide volume concentration of 70-99.8%, air pressure of 0.2-0.4MPa, and curing time of 6-12h to obtain the carbon mineralized electromagnetic protection plate.
[0042] The carbon mineralized electromagnetic protection plate provided by the present invention has a good pore structure and is also doped with conductive fillers to improve the conductivity of the material. The electromagnetic shielding effect in the full frequency band is better than that of traditional cement-based electromagnetic protection plates. The molding process is simple, the molding time is short, and it has excellent mechanical properties, and has good development prospects in the field of special construction.
[0043] The present invention is further described in detail below through specific examples and comparative examples.
[0044] To avoid redundant description, some raw materials in the following embodiments and comparative examples of the present invention are summarized as follows:
[0045] γ-C2S is prepared by mixing calcium hydroxide and silicon dioxide in a molar ratio of 2:1, adding water of equal mass to the mixture of calcium hydroxide and silicon dioxide, and then sintering at 1400°C for 3 hours.
[0046] The foam stabilizer is hydroxypropyl methylcellulose with a viscosity of 100000Cst.
[0047] Example 1 (γ-C2S as main adhesive)
[0048] The solid components are: 75 parts of γ-C2S, 20 parts of cement, 5 parts of quartz sand, and 0.3 parts of HPMC;
[0049] Preparation method:
[0050] According to the proportion, 75 parts of γ-C2S, 20 parts of cement, 5 parts of quartz sand and 30 parts of water and 2 parts of water reducer are added to a stirring device and stirred to form a prefabricated slurry at a stirring speed of 120 r / min and a stirring time of 1 min;
[0051] Since a small amount of foam is unstable, the amount of raw materials used for the foam is increased in the actual configuration process of the present invention, and then used in proportion; 1 part of the weighed plant protein foaming agent, 0.5 part of HPMC and 50 parts of water are mixed according to the ratio, and the foam is prepared by a foaming machine;
[0052] 8 parts of the prepared foam (equivalent to 0.155 parts of the foaming agent actually added) were added to the prefabricated slurry, and stirred with a stirring device to form a target slurry at a stirring speed of 120 r / min and a stirring time of 30 s;
[0053] Pour the target slurry into a 180mm×180mm×20mm mold and cure it in a curing room at 30℃ for 12h;
[0054] After curing, the obtained slab is placed in a reactor and cured in a CO2 atmosphere at a temperature of 40°C, a relative humidity of 50%, an air pressure of 0.2MPa, and a curing time of 12h; the CO2 gas source is a high-concentration CO2 gas enriched from industrial waste gas, and the CO2 volume concentration is 99%;
[0055] After the curing is completed, a carbon mineralized electromagnetic protection plate is obtained.
[0056] Additionally, standard square test blocks with a size of 100mm×100mm×100mm were prepared and their mechanical properties were tested; and electromagnetic protection related tests were performed on the prepared carbon mineralized electromagnetic protection plates.
[0057] According to the national standard GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method", the compressive strength of the matrix test block was 6.7MPa and the dry density was 750±10kg / m 3 The thermal conductivity is 0.13W / m·k; the electromagnetic shielding effectiveness of the electromagnetic protection plate is measured according to the national standard GJB 2038A-2011 "Test method for reflectivity of radar absorbing materials", and the absorption frequency band above 10dB reaches 6.3GHz, and the absorption frequency band above 20dB reaches 1.6GHz.
[0058] Example 2 (adding carbon fiber)
[0059] The solid components are: 75 parts of γ-C2S, 20 parts of cement, 5 parts of quartz sand, 0.3 parts of HPMC, and 2 parts of carbon fiber;
[0060] Preparation method:
[0061] According to the proportion, 75 parts of γ-C2S, 20 parts of cement, 5 parts of quartz sand and 35 parts of water and 2 parts of water reducing agent were added to the stirring device and stirred to form a prefabricated slurry at a stirring speed of 120 r / min and a stirring time of 1 min;
[0062] Add 2 parts of carbon fiber to the prefabricated slurry and stir evenly at a stirring speed of 120 r / min for 30 s.
[0063] According to the ratio, 1 part of the weighed plant protein foaming agent, 0.5 part of HPMC and 50 parts of water were mixed, and foam was prepared using a foaming machine;
[0064] Add 10 parts of the prepared foam into the prefabricated slurry and stir with a stirring device to form a target slurry at a stirring speed of 120 r / min and a stirring time of 30 s;
[0065] Pour the target slurry into a 180mm×180mm×20mm mold and cure it in a curing room at 30℃ for 12h;
[0066] After curing, the obtained slab is placed in a reactor and cured in a CO2 atmosphere at a temperature of 40°C, a relative humidity of 50%, an air pressure of 0.2MPa, and a curing time of 12h; the CO2 gas source is a high-concentration CO2 gas enriched from industrial waste gas, and the CO2 volume concentration is 99%;
[0067] After the curing is completed, a carbon mineralized electromagnetic protection plate is obtained.
[0068] Additionally, standard square test blocks with a size of 100mm×100mm×100mm were prepared and their mechanical properties were tested; and electromagnetic protection related tests were performed on the prepared carbon mineralized electromagnetic protection plates.
[0069] According to the national standard GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method", the compressive strength of the matrix test block was 7.0MPa and the dry density was 750±10kg / m 3 The thermal conductivity is 0.17W / m·k; the electromagnetic shielding effectiveness of the electromagnetic protection plate is measured according to the national standard GJB 2038A-2011 "Test method for reflectivity of radar absorbing materials", and the absorption frequency band above 10dB reaches 9.8GHz, and the absorption frequency band above 20dB reaches 4.1GHz.
[0070] Example 3 (adding graphite powder)
[0071] The solid components are: 75 parts of γ-C2S, 20 parts of cement, 5 parts of quartz sand, 0.3 parts of HPMC, and 5 parts of graphite powder;
[0072] Preparation method:
[0073] According to the proportion, 75 parts of γ-C2S, 20 parts of cement, 5 parts of graphite powder, 5 parts of quartz sand and 45 parts of water and 2 parts of water reducing agent were added into a stirring device and stirred to form a prefabricated slurry at a stirring speed of 120 r / min and a stirring time of 1.5 min.
[0074] According to the ratio, 1 part of the weighed plant protein foaming agent, 0.5 part of HPMC and 50 parts of water were mixed, and foam was prepared using a foaming machine;
[0075] Add 12 parts of the prepared foam to the prefabricated slurry, and stir with a stirring device to form a target slurry at a stirring speed of 120 r / min and a stirring time of 30 s;
[0076] Pour the target slurry into a 180mm×180mm×20mm mold and cure it in a curing room at 30℃ for 12h;
[0077] After curing, the obtained slab is placed in a reactor and cured in a CO2 atmosphere at a temperature of 40°C, a relative humidity of 50%, an air pressure of 0.2MPa, and a curing time of 12h; the CO2 gas source is a high-concentration CO2 gas enriched from industrial waste gas, and the CO2 volume concentration is 99%;
[0078] After the curing is completed, a carbon mineralized electromagnetic protection plate is obtained.
[0079] Additionally, standard square test blocks with a size of 100mm×100mm×100mm were prepared and their mechanical properties were tested; and electromagnetic protection related tests were performed on the prepared carbon mineralized electromagnetic protection plates.
[0080] According to the national standard GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method", the compressive strength of the matrix test block was 5.8MPa and the dry density was 750±10kg / m 3 The thermal conductivity is 0.16W / m·k; the electromagnetic shielding effectiveness of the electromagnetic protection plate is measured according to the national standard GJB2038A-2011 "Test method for reflectivity of radar absorbing materials", and the absorption frequency band above 10dB reaches 9.1GHz, and the absorption frequency band above 20dB reaches 3.7GHz.
[0081] Example 4 (Carbon mineralized composite electromagnetic protection plate)
[0082] The solid components are: 75 parts of γ-C2S, 20 parts of cement, 5 parts of quartz sand, 0.3 parts of HPMC, 3 parts of graphite powder, and 1 part of carbon fiber;
[0083] Preparation method:
[0084] According to the proportion, 75 parts of γ-C2S, 20 parts of cement, 3 parts of graphite powder, 5 parts of quartz sand and 45 parts of water and 2 parts of water reducing agent were added into a stirring device and stirred to form a prefabricated slurry at a stirring speed of 120 r / min and a stirring time of 1.5 min.
[0085] Add 2 parts of carbon fiber to the prefabricated slurry and stir evenly at a stirring speed of 120 r / min for 30 s.
[0086] According to the ratio, 1 part of the weighed plant protein foaming agent, 0.5 part of HPMC and 50 parts of water were mixed, and foam was prepared using a foaming machine;
[0087] Add 10 parts of the prepared foam into the prefabricated slurry and stir with a stirring device to form a target slurry at a stirring speed of 120 r / min and a stirring time of 30 s;
[0088] Pour the target slurry into a 180mm×180mm×20mm mold and cure it in a curing room at 30℃ for 12h;
[0089] After curing, the obtained slab is placed in a reactor and cured in a CO2 atmosphere at a temperature of 40°C, a relative humidity of 50%, an air pressure of 0.2MPa, and a curing time of 12h; the CO2 gas source is a high-concentration CO2 gas enriched from industrial waste gas, and the CO2 volume concentration is 99%;
[0090] After the curing is completed, a carbon mineralized electromagnetic protection plate is obtained.
[0091] Additionally, standard square test blocks with a size of 100mm×100mm×100mm were prepared and their mechanical properties were tested; and electromagnetic protection related tests were performed on the prepared carbon mineralized electromagnetic protection plates.
[0092] According to the national standard GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method", the compressive strength of the matrix test block was 6.9MPa and the dry density was 750±10kg / m 3 The thermal conductivity is 0.15W / m·k; the electromagnetic shielding effectiveness of the electromagnetic protection plate is measured according to the national standard GJB 2038A-2011 "Test method for reflectivity of radar absorbing materials", and the absorption frequency band above 10dB reaches 10.4GHz, and the absorption frequency band above 20dB reaches 4.8GHz.
[0093] Comparative Example 1 (cement as adhesive)
[0094] Solid components are: 95 parts of cement, 5 parts of quartz sand, and 0.3 parts of HPMC;
[0095] Preparation method:
[0096] According to the proportion, 95 parts of cement, 5 parts of quartz sand, 20 parts of water and 1 part of water reducer are added to the stirring device and stirred to form a prefabricated slurry. The stirring speed is 120r / min and the stirring time is 1min.
[0097] According to the ratio, 1 part of the weighed plant protein foaming agent, 0.5 part of HPMC and 50 parts of water were mixed, and foam was prepared using a foaming machine;
[0098] Add 7 parts of the prepared foam to the prefabricated slurry, stir with a stirring device to form a target slurry, the stirring speed is 120 r / min, and the stirring time is 30 s;
[0099] Pour the target slurry into a 180mm×180mm×20mm mold and cure it in a curing room at 30℃ for 12h;
[0100] After static curing, the obtained slab is placed in a curing room with a curing temperature of 25° C. and a relative humidity of 95% for standard curing for 7 days.
[0101] After the curing is completed, a cement-based electromagnetic protection plate is obtained.
[0102] Additionally, standard square test blocks with a size of 100mm×100mm×100mm were prepared and their mechanical properties were tested; and electromagnetic protection related tests were performed on the prepared carbon mineralized electromagnetic protection plates.
[0103] According to the national standard GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method", the compressive strength of the matrix test block was 5.7MPa and the dry density was 750±10kg / m 3 The thermal conductivity is 0.14W / m·k; the electromagnetic shielding effectiveness of the electromagnetic protection plate is measured according to the national standard GJB 2038A-2011 "Test method for reflectivity of radar absorbing materials", and the absorption frequency band above 10dB reaches 5.1GHz, and the absorption frequency band above 20dB reaches 0.9GHz.
[0104] Comparative Example 2 (cement + carbon fiber)
[0105] Solid components are: 95 parts of cement, 5 parts of quartz sand, 0.3 parts of HPMC, and 2 parts of carbon fiber;
[0106] Preparation method:
[0107] According to the proportion, 95 parts of cement, 5 parts of quartz sand, 25 parts of water and 1 part of water reducer are added to a stirring device and stirred to form a prefabricated slurry. The stirring speed is 120r / min and the stirring time is 1min.
[0108] Add 2 parts of carbon fiber to the prefabricated slurry and stir evenly at a stirring speed of 120 r / min for 30 s.
[0109] According to the ratio, 1 part of the weighed plant protein foaming agent, 0.5 part of HPMC and 50 parts of water were mixed, and foam was prepared using a foaming machine;
[0110] Add 9 parts of the prepared foam to the prefabricated slurry and stir with a stirring device to form a target slurry at a stirring speed of 120 r / min and a stirring time of 30 s;
[0111] Pour the target slurry into a 180mm×180mm×20mm mold and cure it in a curing room at 30℃ for 12h;
[0112] After static curing, the obtained slab is placed in a curing room with a curing temperature of 25° C. and a relative humidity of 95% for standard curing for 7 days.
[0113] After the curing is completed, a cement-based electromagnetic protection plate is obtained.
[0114] Additionally, standard square test blocks with a size of 100mm×100mm×100mm were prepared and their mechanical properties were tested; and electromagnetic protection related tests were performed on the prepared carbon mineralized electromagnetic protection plates.
[0115] According to the national standard GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method", the compressive strength of the matrix test block was 5.6MPa and the dry density was 750±10kg / m 3 The thermal conductivity is 0.17W / m·k; the electromagnetic shielding effectiveness of the electromagnetic protection plate is measured according to the national standard GJB 2038A-2011 "Test method for reflectivity of radar absorbing materials", and the absorption frequency band above 10dB reaches 8.3GHz, and the absorption frequency band above 20dB reaches 3.0GHz.
[0116] Comparative Example 3 (cement + graphite powder)
[0117] Solid components are: 95 parts of cement, 5 parts of quartz sand, 0.3 parts of HPMC, and 5 parts of graphite powder;
[0118] Preparation method:
[0119] According to the proportion, 95 parts of cement, 5 parts of graphite powder, 5 parts of quartz sand and 25 parts of water and 1 part of water reducer are added into a stirring device and stirred to form a prefabricated slurry at a stirring speed of 120 r / min and a stirring time of 1.5 min;
[0120] According to the ratio, 1 part of the weighed plant protein foaming agent, 0.5 part of HPMC and 50 parts of water were mixed, and foam was prepared using a foaming machine;
[0121] Add 11 parts of the prepared foam to the prefabricated slurry, and stir with a stirring device to form a target slurry at a stirring speed of 120 r / min and a stirring time of 30 s;
[0122] Pour the target slurry into a 180mm×180mm×20mm mold and cure it in a curing room at 30℃ for 12h;
[0123] After static curing, the obtained slab is placed in a curing room with a curing temperature of 25° C. and a relative humidity of 95% for standard curing for 7 days.
[0124] After the curing is completed, a cement-based electromagnetic protection plate is obtained.
[0125] Additionally, standard square test blocks with a size of 100mm×100mm×100mm were prepared and their mechanical properties were tested; and electromagnetic protection related tests were performed on the prepared carbon mineralized electromagnetic protection plates.
[0126] According to the national standard GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method", the compressive strength of the matrix test block was 5.8MPa and the dry density was 750±10kg / m 3 The thermal conductivity is 0.16W / m·k; the electromagnetic shielding effectiveness of the electromagnetic protection plate is measured according to the national standard GJB 2038A-2011 "Test method for reflectivity of radar absorbing materials", and the absorption frequency band above 10dB reaches 7.6GHz, and the absorption frequency band above 20dB reaches 2.7GHz.
[0127] Comparative Example 4 (cement-based composite electromagnetic protection plate)
[0128] The solid components are: 95 parts of cement, 5 parts of quartz sand, 0.3 parts of HPMC, 3 parts of graphite powder, and 1 part of carbon fiber;
[0129] Preparation method:
[0130] According to the proportion, 95 parts of cement, 3 parts of graphite powder, 5 parts of quartz sand and 45 parts of water and 2 parts of water reducing agent were added into a stirring device and stirred to form a prefabricated slurry at a stirring speed of 120 r / min and a stirring time of 1.5 min;
[0131] Add 2 parts of carbon fiber to the prefabricated slurry and stir evenly at a stirring speed of 120 r / min for 30 s.
[0132] According to the ratio, 1 part of the weighed plant protein foaming agent, 0.5 part of HPMC and 50 parts of water were mixed, and foam was prepared using a foaming machine;
[0133] Add 9 parts of the prepared foam to the prefabricated slurry and stir with a stirring device to form a target slurry at a stirring speed of 120 r / min and a stirring time of 30 s;
[0134] Pour the target slurry into a 180mm×180mm×20mm mold and cure it in a curing room at 30℃ for 12h;
[0135] After static curing, the obtained slab is placed in a curing room with a curing temperature of 25° C. and a relative humidity of 95% for standard curing for 7 days.
[0136] After the curing is completed, a cement-based electromagnetic protection plate is obtained.
[0137] Additionally, standard square test blocks with a size of 100mm×100mm×100mm were prepared and their mechanical properties were tested; and electromagnetic protection related tests were performed on the prepared carbon mineralized electromagnetic protection plates.
[0138] According to the national standard GB / T 11969-2020 "Autoclaved Aerated Concrete Performance Test Method", the compressive strength of the matrix test block was 6.5MPa and the dry density was 750±10kg / m 3 The thermal conductivity is 0.16W / m·k; the electromagnetic shielding effectiveness of the electromagnetic protection plate is measured according to the national standard GJB 2038A-2011 "Test method for reflectivity of radar absorbing materials", and the absorption frequency band above 10dB reaches 8.9GHz, and the absorption frequency band above 20dB reaches 3.6GHz.
[0139] The above examples and comparative examples were statistically analyzed and the results are shown in Table 1 below.
[0140] Table 1 Test results of various embodiments of the present invention and comparative examples
[0141]
[0142]
[0143] As shown in Table 1, the carbonized cementitious material is used as the main cementitious material component in Examples 1-4 of the present invention, and a small amount of cement is compounded to achieve or even exceed the strength of the pure cement-based electromagnetic protection plate obtained in Comparative Examples 1-4, with a strength of 5.8-7.0 MPa. By controlling the amount of foam added and coordinating with other raw materials, the dry density is ensured to be 750±10 kg / m 3 range; the thermal conductivity of the carbon mineralized electromagnetic protection plate obtained in Example 1-4 is the same as or slightly lower than that of the pure cement-based electromagnetic protection plate obtained in Comparative Example 1-4, indicating that the thermal insulation performance is slightly improved; and the carbon mineralized electromagnetic protection plate obtained in Example 1-4 has better electromagnetic protection performance, with an absorption frequency band above 10dB reaching 6.3 to 10.4GHz, and an absorption frequency band above 20dB reaching 3.7 to 4.8GHz.
[0144] By comparing Examples 1-4 at the same time, it can be seen that the use of carbon fiber as the conductive filler in Example 2 of the present invention is better than the use of graphite as the conductive filler in Example 3, and the use of pure graphite powder as the conductive filler of the present invention will reduce the strength of the obtained electromagnetic protection plate; in Example 4, graphite powder and carbon fiber are used in combination, which produces a synergistic effect.
[0145] Carbon fiber is an inorganic polymer fiber with a carbon content of more than 90%. It has a chaotic graphite structure inside, which is similar to the microstructure of artificial graphite, so it has good electrical conductivity. Graphite is a single carbon with a multilayer structure. The layers are arranged in a honeycomb hexagonal shape. Each carbon atom is connected to three other carbon atoms. Electrons are easily transmitted between layers, so graphite has good electrical conductivity. As carbon-based materials, carbon fiber and graphite powder have excellent electrical conductivity. Adding them to cement-based materials can enhance the electrical conductivity and electromagnetic shielding performance of the materials. In the experiment, it was found that when the volume fraction of graphite powder reaches a certain value, further increasing the dosage will have limited effect on the further improvement of electromagnetic shielding effectiveness. With the increase of the volume fraction of graphite powder, the water-solid ratio of the prefabricated slurry will be greatly increased, resulting in a significant decrease in compressive strength. As a filler, carbon fiber basically does not affect the water-solid ratio at low dosage, and it plays a network connection role in the material matrix, slightly enhancing the mechanical properties. When the dosage continues to increase, the water-solid ratio increases and the compressive strength continues to decrease. Therefore, in the raw material system of the present invention, the amount of the conductive filler used is 1 to 5 parts.
[0146] Compared with the prior art, the present invention provides an electromagnetic protection plate and a preparation method thereof, the electromagnetic protection plate comprises the following raw materials in parts by weight: 60-80 parts of carbonized gelling material, 20-40 parts of cement, 10-20 parts of inert filler, 1.5-2 parts of polycarboxylic acid water reducer, 1-5 parts of conductive filler, 1-1.5 parts of foaming agent, 0.3-0.5 parts of foam stabilizer and 25-35 parts of water. The preparation method of the present invention is simple, requires fewer types of raw materials, has low cost and short molding time; by introducing a large number of pore structures, the plate is endowed with excellent wave absorbing properties; the conductive filler with good electrical conductivity is added to enable the plate to obtain excellent shielding properties, and also plays the role of filler, so that the slurry after adding foam has good stability and is not easy to settle; the gelling component used in the present invention has excellent CO2 reaction activity, can undergo mineralization reaction with CO2, and solidify a large amount of CO2 while forming excellent mechanical properties, which is in line with the concept of green energy saving and emission reduction. The carbon mineralized electromagnetic protection plate of the present invention has excellent electromagnetic protection performance and mechanical properties. It can be used in the field of electromagnetic shielding, can achieve a good electromagnetic shielding effect, effectively deal with electromagnetic radiation outside the area, and at the same time meet the requirements of the building structure. It can be used as a wave absorber and building exterior wall in the military and civilian special function building fields and has good application prospects.
[0147] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. An electromagnetic protection plate, characterized in that: The composition is composed of the following raw materials by weight: 60-80 parts of carbonized cementitious material, 20-40 parts of cement, 10-20 parts of inert filler, 1.5-2 parts of water reducing agent, 1-5 parts of conductive filler, 0.1-0.25 parts of foaming agent, 0.03-0.08 parts of foam stabilizer and several parts of water; The carbonized gelling material is γ-C2S; The method for preparing the electromagnetic protection plate comprises the following steps: mixing the carbonized cementitious material, cement, an inert filler, a water reducing agent and a conductive filler to obtain an initial slurry; Mixing a foaming agent, a foam stabilizer and water to prepare foam; Mixing the initial slurry with the foam to obtain a target slurry; The target slurry is sequentially cast, cured, demoulded and carbonized to obtain the electromagnetic protection plate.
2. The electromagnetic protection plate according to claim 1, characterized in that: The cement is ordinary Portland cement with a grade of ≥42.
5.
3. The electromagnetic protection plate according to claim 1, characterized in that: The inert filler includes one or more of fly ash, quartz sand powder and limestone powder.
4. The electromagnetic protection plate according to claim 1, characterized in that: The conductive filler is one or more of chopped carbon fiber and graphite powder.
5. The electromagnetic protection plate according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer with a solid content of ≥30%.
6. The electromagnetic protection plate according to claim 1, characterized in that: The foaming agent is one or more of a plant protein foaming agent, an animal protein foaming agent and an air entraining agent; and the foam stabilizing agent is hydroxypropyl methylcellulose.
7. The electromagnetic protection plate according to claim 1, characterized in that: Resting means placing it in a forced air drying oven at 30~50℃ for 2 days.
8. The electromagnetic protection plate according to claim 1, characterized in that: The conditions for carbonization curing are: carbonization temperature is 5~40℃, relative humidity is 10~60%, carbon dioxide volume concentration is 70~99.8%, air pressure is 0.2~0.4MPa, and curing time is 6~12h.
Citation Information
Patent Citations
Recycled fine aggregate aerated building block with electromagnetic wave absorption performance and preparation method thereof
CN111995340A